Interleukin‐21 administration to aged mice rejuvenates their peripheral T‐cell pool by triggering de novo thymopoiesis. Issue 2 (13th January 2016) - Al‐Chami, E.; Tormo, A.; Pasquin, S.; Kanjarawi, R.; Ziouani, S.; Rafei, M.
Summary: The vaccination efficacy in the elderly is significantly reduced compared to younger populations due to thymic involution and age‐related intrinsic changes affecting their naïve T‐cell compartment. Interleukin (IL)‐21 was recently shown to display thymostimulatory properties. Therefore, we hypothesized that its administration to ageing hosts may improve T‐cell output and thus restore a competent peripheral T‐cell compartment. Indeed, an increase in the production of recent thymic emigrants (RTEs) attributable to intrathymic expansion of early thymic progenitors (ETPs), double‐negative (DN), and double‐positive (DP) thymocytes as well as thymic epithelial cell (TEC) was observed in recombinant (r)IL‐21‐treated aged mice. In sharp contrast, no alterations in the frequency of bone marrow (BM)‐derived progenitors were detected following rIL‐21 administration. Enhanced production of naïve T cells improved the T‐cell receptor (TCR) repertoire diversity and re‐established a pool of T cells exhibiting higher levels of miR‐181a and diminished amounts of the TCR‐inhibiting phosphatases SHP‐2 and DUSP5/6. As a result, stimulation of T cells derived from rIL‐21‐treated aged mice displayed enhanced activation of Lck, ZAP‐70, and ERK, which ultimately boosted their IL‐2 production, CD25 expression, and proliferation capabilities in comparison with T cells derived from control aged mice. Consequently, aged rIL‐21‐treated mice vaccinated using a tyrosinase‐related protein 2 (Trp2)‐derived peptide exhibited a substantial delay in B16 tumor growth and improved survival. The results of this study highlight the immunorestorative function of rIL‐21 paving its use as a strategy for the re‐establishment of effective immunity in the elderly.